2020
DOI: 10.1093/texcom/tgaa068
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Comparison of Inhibitory Interneuron Size and Distribution between Mouse and Macaque V1, Using Calcium-Binding Proteins

Abstract: The mouse is a useful and popular model for studying of visual cortical function. To facilitate the translation of results from mice to primates, it is important to establish the extent of cortical organization equivalence between species and to identify possible differences. We focused on the different types of interneurons as defined by calcium binding protein (CBP) expression in the layers of primary visual cortex (V1) in mouse and rhesus macaque. CBPs parvalbumin (PV), calbindin (CB), and calretinin (CR) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
30
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 87 publications
9
30
2
Order By: Relevance
“…This, in turn, increases the delay between EPSP input and spike output [22,35,36]. This slower EPSP-spike coupling compared with that of rodent basket cells results, at least partly, from a lower density of persistently open membrane ion channels at the resting potential and concomitantly higher resting input resistance, which leads to slower membrane potential kinetics [40,54,69,[79][80][81]. Our experiments and simulations revealed that robust expression of voltage-sensitive HCN channels at the human basket cell soma membrane can increase membrane ion leak at the resting potential and thus accelerate EPSP-spike transformation.…”
Section: Perisomatic Hcn Channels In Human Fast-spiking Cells Ensure ...mentioning
confidence: 99%
“…This, in turn, increases the delay between EPSP input and spike output [22,35,36]. This slower EPSP-spike coupling compared with that of rodent basket cells results, at least partly, from a lower density of persistently open membrane ion channels at the resting potential and concomitantly higher resting input resistance, which leads to slower membrane potential kinetics [40,54,69,[79][80][81]. Our experiments and simulations revealed that robust expression of voltage-sensitive HCN channels at the human basket cell soma membrane can increase membrane ion leak at the resting potential and thus accelerate EPSP-spike transformation.…”
Section: Perisomatic Hcn Channels In Human Fast-spiking Cells Ensure ...mentioning
confidence: 99%
“…CR is expressed in most VIP neurons in primate cortex (Gabbott and Bacon, 1997;Lake et al, 2016), and both VIP and CR show a similar expression across layers and cortical areas in the macaque (Dienel et al, 2020). However, the investigation of cross-species interneuron type similarities and differences is ongoing and not resolved (Hodge et al, 2019;Kooijmans et al, 2020;Krienen et al, 2020). In our model, the three interneuron types should be more appropriately interpreted according to their synaptic targets, rather than other cellular markers.…”
Section: Description Of the Local Cortical Circuitmentioning
confidence: 99%
“…Different interneuron subtypes exhibit distinctive distributions across the six neocortical layers- CR+ and CB+ interneurons neurons are primarily located superficially in layers 1-3 while PV+ neurons are localized principally in layers 2-4. (Conde et al, 1994; DeFelipe; Disney & Aoki, 2008; Dombrowski et al, 2001; Kooijmans et al, 2014; Kooijmans et al, 2020; Tremblay et al, 2016; van Brederode et al, 1990; Zaitsev et al, 2005; Zaitsev et al, 2009). How these neurochemically distinct subpopulations of interneurons compare across species and cortical areas is poorly understood.…”
Section: Introductionmentioning
confidence: 99%